The impact of body mass and skill level on rowing kinematics - Richter, C.; Hamilton, S.; Roemer, K. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
Rowing is a non-weight-bearing aerobic full body exercise, which is often recommended for weight loss programs. Previous studies demonstrated that Body Mass Index (BMI) is correlated with changes in the kinematics of humans. We extend this area of research to compare the effect of both BMI and skill-level on the kinematics of the lower extremities during rowing. Findings highlight differences such as knee flexion, knee internal rotation, hip extension, hip external rotation between normal weight and obese individuals. These findings suggest that injury risks are correlated to body type and previous skill level. This research indicates the need for adjustable setups for the rowing ergometer. This recommendation would not only increase comfort for all types of athletes, but reduce risks of injury and create the necessary conditions to accomplish a proper technique.